ANALISIS PERLINDUNGAN HUKUM TERHADAP DEBITUR GADAI EMAS DI ACEH - Nansadiqa, Lisa (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
This research was conducted to analyze and see how the law complies with the concept of gold pawn financing at bank syariah Indonesia Region l Aceh. In the statutory regulations,the sales process and remaining sales of gold pawn financing collateral objects as well as form of legal protection for gold pawn debtors at bank syariah indonesia Region l Aceh when the price of gold decreases at the time of execution of the pawn object. The analytical method used in this research is empirical normative research, using a statutory approach and a conceptual approach and qualitative analysis. The results of this research indicate that the implementation of the gold pawn financing law at Bank syariah Indonesia is in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council Number 26/DSN-MUI/III/2002 concerning Gold Rahn and the DSN MUI Fatwa Number 25/DSN MUI/III/2002 Concerning Rahn; the practice of pledging gold at Bank Syariah Indonesia in Region I Aceh is carried out based on the standard Operating Procedures applicable to the bank with are then listed on the Gold Pawn Proof Letter (SBGE). However, regarding the method of selling gold pawned objects in BSI Region I Aceh, it is not in accordance with the DSN MUI Fatwa, where the practice of selling pawned objects in BSI Region I Aceh is carried out through sales to gold shops, while the DSN MUI Fatwa regulates the process of selling pawned objects through an auction process. Sharia however, it does not directly violate elements of sharia because it does not violate either.